1992
DOI: 10.3382/ps.0710530
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Viral Genes in Thirteen Highly Inbred Chicken Lines and in Lines Selected for Immune Response Traits

Abstract: Thirteen highly inbred lines of chickens of Leghorn, Spanish, and Egyptian Fayoumi origin, four partly inbred Leghorn lines selected for MHC alleles and immune response to GAT (Ir-GAT), and two replicated, noninbred Leghorn lines divergently selected for multiple immune response traits were subjected to molecular genotyping for endogenous viral (ev) gene sequences. In all highly inbred lines of Leghorn origin, ev1 alone or both ev1 and ev2 were observed. The Spanish and Fayoumi lines had three and five ev gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…The F 1 population was produced in five hatches by crossing four outbred males of a broiler breeder male line [15] with dams of three highly inbred dam lines: one Fayoumi and two MHCcongenic Leghorn lines (G-B1 and G-B2) with inbreeding coefficients of 99% [38]. These inbred lines have been used in many studies of immune response and disease resistance [6,19,20,25]. The genetic distance between the parental lines maximized the feasibility of finding molecular genetic polymorphisms [38].…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The F 1 population was produced in five hatches by crossing four outbred males of a broiler breeder male line [15] with dams of three highly inbred dam lines: one Fayoumi and two MHCcongenic Leghorn lines (G-B1 and G-B2) with inbreeding coefficients of 99% [38]. These inbred lines have been used in many studies of immune response and disease resistance [6,19,20,25]. The genetic distance between the parental lines maximized the feasibility of finding molecular genetic polymorphisms [38].…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Few such probes are currently available because they require cloning of flanking regions from genomic DNA of birds carrying only one ev insertion, and such birds are rare. An eul-specific probe showed that the genomic insertion site for eul was not occupied by a viral insert in Fayoumi chickens although they carried the restriction fragments usually associated with an eul occupied site in White Leghorns, ie 9.5 kb with SacI and 5.2 kb with BamHI (Lamont et al, 1992). A similar approach revealed a much lower frequency of occupation of the eul site in White Plymouth Rock chickens than in White Leghorns (Aarts et al, 1991).…”
mentioning
confidence: 97%
“…This observation suggested that ev genes expressing envelope antigens, such as ev6, may confer a selective advantage (Robinson et al, 1981), which could explain the ubiquity of ev6. However, ev6 was found to be associated with higher susceptibility to Marek's disease (Kuhnlein et al, 1989b) and lower immunoresponsiveness (Lamont et al, 1992). (Gavora et al, 1991) or to linkage with production trait genes for silent ev genes (Kuhnlein et al, 1989b).…”
mentioning
confidence: 99%
See 2 more Smart Citations